Pengaruh Live Streaming Selling, Diskon, Gratis Ongkir dan Cash on Delivery terhadap Keputusan Pembelian pada E-Commerce Shopee - Arwana, Dyeo Setya; Purnomo, Nanto (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to examine the influence of various factors on purchasing decisions in the e-commerce platform Shopee. Through data collection and analysis, the following conclusions are drawn: Firstly, live streaming selling significantly impacts purchasing decisions on Shopee, indicating an increase in the number of purchases when live streaming selling is utilized. Secondly, discounts have a positive and significant effect on purchasing decisions, as offering discounts or price reductions increases the likelihood of purchases on Shopee. Thirdly, free shipping vouchers significantly influence purchasing decisions, demonstrating that providing free shipping incentives can boost the number of purchases on Shopee. Lastly, cash on delivery (COD) also positively affects purchasing decisions on Shopee, as it facilitates transactions and contributes to higher purchase rates. These findings shed light on the importance of various marketing strategies in driving consumer behavior on e-commerce platforms like Shopee. Keywords: Cash On Delivery, Free Shipping Discounts, Live Streaming Selling, Purchase Decisions, Shopee.